„Sen duszy” w pismach Afrahata - Uciecha, Andrzej (Vox Patrum, 2015)
The soul in the ascetic teaching of Aphrahat was understood as being the element which gave life to the body. Properly nurtured it guaranteed the ascetic a moral development. This role of the soul as the foundation of life influenced his outlook on morality and sensuality. The answer to the biblical „living soul” was in his Demonstrations. This implied a spiritual energy, which every person is born with, which is eternal and adorned with a sensitivity of thought. Death embraced both the body and the soul, except that, for the „living soul”, it was equated with sleep. Analysing the anthropological terminology exposed a strong influence of biblical concepts. The Semitic character of this Persian’s anthropology created problems in the precise indication of the semantic bounds of these ideas. The search was not limited only to seeking out the exclusive character of individual human attributes, but also to try to discover their association and interdependence. From the anthropological material of ascetic teaching in the Demonstrations emerges a vision of a man integrated, in whom the corporal is subjected to the spirit and the external signs (speech and conduct) are in harmony with the internal (thought and feelings).